Report of the third Meeting of Regional [Fishery] Body Secretariats Network : Rome, 7-8 February 2011. - Meeting of Regional Fishery Body Secretariats Network 2 011 : Rome, Italy); Food and Agriculture Organization of the United Nations (Rome : Food and Agriculture Organization of the United Nations, 2011)
The Third Meeting of Regional Fishery Body Secretariats Network (RSN -3) was held in Rome, Italy, from 7 to 8 February 2011. It addressed ma ny pressing issues relating to global and regional fisheries governance , including illegal, unreported and unregulated (IUU) fishing, overcapa city, the ecosystem approach to fisheries management, small-scale and i nland fisheries and the outcomes of the twenty-ninth Session of FAO Com mittee on Fisheries (COFI) held in Rome during the previous week. Twent y-eight Regional Fishery Body (RFB) Secretariats were represented at th e meeting with varying responsibilities over inland, coastal and marine fisheries and aquaculture, as well as four intergovernmental organizat ions. The meeting reached a number of conclusions regarding matters tha t merit the attention of RFBs, governments and FAO. The RSN also issued a Statement responding to unsubstantiated information that had been pu blished about RFBs and elaborating the challenges and achievements of R FBs.
"FIPI/R980 (En)."
Also available on the World Wide Web.
Keywords: Fishery management -- Congresses; Fisheries -- Congresses